Evaluating the viability of a mobile phone-based, SMS/GPRS-enabled, client data collection channel for urban microfinance - Gogineni, Mahesh; Ratan, Aishwarya (2007)
Ujjivan is a young microfinance institution (MFI) headquartered in the southern Indian city of Bangalore (operations commenced in 2004), providing microfinance services to urban low-income households (earning between Rs. 2000 and Rs. 7000 in household income per month). They operate as a Non-Banking Finance Company (NBFC), primarily providing loan products (along with some savings) to working women from these households. They also facilitate the purchase of life insurance policies for their members. Outreach (as of May 2007) stood at 24,100 clients in Bangalore, served through 13 branches, each of which employ 8 loan officers, a Branch Manager and an Accountant. The organization, however, is scaling rapidly in Bangalore and expanding to other Indian cities, and expects outreach to grow three-fold and revenues to grow four-fold over the next financial year. For this reason, the efficiency of their new customer acquisition process has become even more critical to the overall success of the organization‟s operations.